2021
DOI: 10.3389/fonc.2021.727984
|View full text |Cite
|
Sign up to set email alerts
|

Prediction Model of Pathologic Central Lymph Node Negativity in cN0 Papillary Thyroid Carcinoma

Abstract: BackgroundMost patients with papillary thyroid carcinoma (PTC) have an excellent prognosis. Although central lymph node invasion is frequent, management via central lymph node dissection (CLND) remains controversial. The present study retrospectively investigated independent predictors of pathologic central lymph node negativity (pCLN-) and established a prediction model for pCLN- in clinical lymph node negativity (cN0) PTC.MethodsA total of 2,687 patients underwent thyroid surgery for cN0 PTC from 2013 to 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…We noticed that currently, many investigators are developing CLNM risk strati cation prediction tools incorporating many risk factors to help evaluate the need for CLND. Yet among these, few studies have focused on the likelihood of CLNM in the mono-focal, encapsulated group of PTC, underestimating the risk of CLNM in this group of patients whom have traditionally been considered as low cervical lymph node involvement risk group among all PTC patients [13][14][15]. Our study innovatively reviewed data from 1014 mono-focal and encapsulated PTC patients to better assist clinicians in making decisions about whether to perform CLND, and the frequency of postoperative follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We noticed that currently, many investigators are developing CLNM risk strati cation prediction tools incorporating many risk factors to help evaluate the need for CLND. Yet among these, few studies have focused on the likelihood of CLNM in the mono-focal, encapsulated group of PTC, underestimating the risk of CLNM in this group of patients whom have traditionally been considered as low cervical lymph node involvement risk group among all PTC patients [13][14][15]. Our study innovatively reviewed data from 1014 mono-focal and encapsulated PTC patients to better assist clinicians in making decisions about whether to perform CLND, and the frequency of postoperative follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Relatively, the CLNM rates for mono-focal PTC patients without gross ETE by preoperative US were generally low, and these patients are the main candidates for active surveillance (AS) [13]. However, relevant research data showed that even for those without ETE or multifocality, the incidence rate of CLNM was still up to about 30% [13][14][15]. To the best of our knowledge, although several studies have been conducted on the prediction of CLNM for PTC patients, none of them have focused on mono-focal patients with preoperatively-con rmed encapsulated tumor, who have long been thought as low CLNM risk subgroup.…”
Section: Introductionmentioning
confidence: 99%
“…The dissection of the central compartment was considered level VI and included the prelaryngeal, pretracheal, and paratracheal lymph nodes. The lateral lymph nodes involve levels II, III, IV, and V. The surgical procedure has been described in our previous studies [14,15]. The central lymph nodes were examined by intraoperative frozen section evaluation conducted by two senior pathologists.…”
Section: Surgical Approachmentioning
confidence: 99%
“…The 2022 National Comprehensive Cancer Network (NCCN) advises against utilizing prophylactic CLND to treat T1 and T2 cN0 PTC ( 5 ). Nevertheless, the sensitivity of preoperative detection, such as ultrasound, is low for assessing the central lymph node (CLN) state ( 6 ); thus, the high probability of occult CLNM cannot be ignored even in cN0 PTMCs ( 7 ).…”
Section: Introductionmentioning
confidence: 99%